Macrocarpal I induces immunogenic cell death and synergizes with immune checkpoint inhibition by targeting tubulin and PARP1 in colorectal cancer - Yaxin Zhang; Huali Li; Yali Zhao; Lingtao Liu; Yi Zhou; Xingyan Pan; Yanqing Ding; Wenting Liao; Lu Qi; Chengmei Huang; Na Tang (Cell Death Discovery)
Abstract Colorectal cancer (CRC) presents an obstacle to immunotherapy, primarily because most cases are microsatellite stable (MSS) tumors, which are often described as “cold tumors” with limited immunogenicity. Recent studies have indicated that several therapeutic approaches, such as chemotherapy and targeted therapies, can elicit immunogenic cell death (ICD) and stimulate immune responses. However, challenges such as target affinity and in vivo pharmacokinetics limit the efficacy and immune response of current targeted therapies. In this study, we demonstrate that Macrocarpal I is a potent inducer of ICD by activating the PERK/eIF2A/ATF4/CHOP signaling pathway. Furthermore, Macrocarpal I induces apoptosis and ferroptosis, both of which act as triggers for ICD. Mechanistically, Macrocarpal I directly targets TUBB2B and PARP1, disrupting microtubule polymerization and DNA repair processes. Importantly, treatment with Macrocarpal I enhances the anti-tumor immune response and augments responsiveness to anti-PD-1 therapy in an MC38 syngeneic mouse model of CRC.